A perspective on the use of the cervical flexion rotation test in the physical therapy management of cervicogenic headaches - Jean-Philippe Paquin; Jean-Pierre Dumas; Thomas Gérard; Yannick Tousignant-Laflamme (Archives of Physiotherapy, 2022)
Abstract Background The Cervical Flexion-Rotation Test (CFRT) is widely used in the assessment of upper cervical spine mobility impairments and in the diagnosis of cervicogenic headache (CGH) by physiotherapist. Many studies investigated its different properties, and the results show that the CFRT has good construct validity in the measurement of C1-C2 rotation as well as good to excellent reliability. Purpose In this theoretical paper, we explore the value and point out two methodological issues associated to the CFRT, one related to the procedures and another related to its diagnostic accuracy. Results Our analysis indicate that there are many confounding factors that could affect the CFRT cut-off’s accuracy, which are likely to overestimate the diagnosis properties of CFRT. Potential solutions are discussed. Moreover, the gold standard (manual examination) used to examine the validity of the CFRT for the diagnosis of CGH appears to be far from perfect - we could argue that the diagnostic properties of the CFRT for CGH might be biased and the likelihood ratios are likely to be overestimated. However, it could be relevant to explore if results of the CFRT could be considered as a treatment-effect modifier. Maybe the CFRT could be more valuable as a prognostic factor? Conclusion The quality of evidence supporting the validity of the CFRT is most likely biased. In the absence of a better gold standard, maybe the CFRT could be a more valuable test to establish the patient’s prognosis and help the clinician to choose the most appropriate treatment options.